Sustentabilidade por meio da indústria 4.0 e produção mais limpa: Múltiplos casos na indústria automotiva - Silva, Aleksander da Conceição (2021)
The new evolution of the productive and industrial process called Industry 4.0 (I4.0) and its related technologies, such as the Internet of Things, big data analysis and cyberphysical systems, still have an unknown impact on the use of production practices cleaner (CP) to promote sustainability in the industry. Therefore, this paper aims to analyze the economic, environmental and social benefits of applying industry 4.0 technologies through the cleaner production practices in an automobile company. The method adopted was a systematic literature review, followed by a study of multiple cases in the automotive sector. The results showed that the combination of industry 4.0 technologies adopted in a process and material handling corroborate to cleaner production practices with a positive impact on the triple bottom line sustainability assessment. In this way, it presented environmental benefits with cleaner production practices with an increase in the life cycle of inputs, avoided the generation of residues that impact the environment, reduced gas emissions and the use of natural resources, and improved energy efficiency. In addition, it presented economic benefits, through the reduction of labor, energy cost and inputs. And finally, there were social benefits, through improvements in employee well-being, safety and ergonomics. This study highlights the contribution to the practice, because it encourages companies to adopt new technologies in their processes to reduce environmental impact and mitigate costs and material waste. In addition, it collaborates with theory by presenting quantitative tools for environmental impact analysis (MIF), accident risk analysis (FMEA) and the Suzanne Rodgers method for ergonomic assessment, that will helps researchers easily for social assessment. And finally, it contributes to society, which indicates that the adoption of new technologies by companies, in addition to bringing technological benefits to managers, also contributes to better working conditions and allows the reduction of gas emissions into the atmosphere. On the other hand, it offers a warning to society and government, because technological advances increase unemployment, due to the reduction in human intervention, which results in the reduction of less specialized labor.